Rapid Authentication of Pig Leather and Synthetic AlternRapid Authentication of Pig Leather and Synthetic Alternatives using NIR Spectroscopy and Chemometrics Approachatives using NIR Spectroscopy and Chemometrics Approach - Mohd Fared Abdul Khir; Ainil Hawa Mohamad Fauzi; Dzulfadli Rosli; Mohd Sukri Hassan; Norzaliman Mohd Zain (USIM Press, 2026)
Indexed by MYCITE